La formation des prix et les industries canadiennes exposées et abritées : price formation and the Canadian exposed and sheltered industries - Decaluwé, Bernard (L'Actualité économique, 1981)
ABSTRACTFollowing the bursts of inflation registered in the 1970s, many authors pointed to a generalization of the phenomenon of inflation and claimed that in a small economy highly integrated into international markets, the steady rise in general price levels might be attributable to foreign causes. In this context, the "Scandinavian School" gave renewed credibility to the division of the economy into two major categories: sectors exposed to strong international competition and those protected from such competition. In our study, we do not attempt to validate the entire "Scandinavian model", but only to examine the nature of the distinction between exposed and sheltered industries by proposing a list of industries in each of the two categories. In contrast to other work based on the Scandinavian model, the proposed classification presented in this study is based on a measure of the proportion of a sector's output that is exported. Following this arbitrary criterion, we divide the 22 branches of the primary and manufacturing sectors into eleven exposed and eleven sheltered branches. A series of tests are then applied to validate this classification.